Distance learning and the transformation of working conditions in teaching: ICTs and the commodification of education in Brazil. (1st July 2013) - ,; ,
Abstract : As capital transforms education into one more site of investment and accumulation, it has been attempting to introduce into the teaching-learning process methods of work management that combine the Japanese Toyotist philosophy of participative management with Taylorist practices of work organisation. This paper draws on research conducted at a Brazilian private institution providing digitally-supported distance learning to show the connection between capital and labour in this process. It examines how the reification of the teacher contributes to the commodification of education. Teaching is just one example of a sphere in which creative labour is being commodified. These methods thus have parallels in other sectors, and the paper concludes that there is a need for further research into other activities in which capital is attached to creative work in order to generate value, Such research could contribute to a better general understanding of the capital-information process.